2018
DOI: 10.1080/10717544.2018.1477859
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GPC3 antibody-modified sorafenib-loaded nanoparticles significantly inhibited HepG2 hepatocellular carcinoma

Abstract: Sorafenib (SFB) has improved the treatment of hepatocellular carcinoma (HCC) and has fewer severe side effects than other agents used for that purpose. However, due to a lack of tumor-specific targeting, the concentration of the drug in tumor tissue cannot be permanently maintained at a level that inhibits tumor growth. To overcome this problem, we developed a novel SFB-loaded polymer nanoparticle (NP). The NP (a TPGS-b-PCL copolymer that was synthesized from ε-caprolactone and d-α-tocopheryl polyethylene glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Polyester materials, such as poly (d,llactide-co-glycolic acid, PLGA), d-α-tocopheryl polyethylene glycol 1000 succinate(TPGS), and poly(ethylene glycol) (PEG), yield favorable biodegradation products that do not cause sexual or organ damage and have been widely used in controlled release drug-loaded microspheres [16,17]. PLA and PLGA drug-loaded microspheres and NPs protect the drugs, aid their solubilization, and improve their bioavailability and targeted release [18]. However, the hydrophobicity of these two materials limits their use as pharmaceutical carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Polyester materials, such as poly (d,llactide-co-glycolic acid, PLGA), d-α-tocopheryl polyethylene glycol 1000 succinate(TPGS), and poly(ethylene glycol) (PEG), yield favorable biodegradation products that do not cause sexual or organ damage and have been widely used in controlled release drug-loaded microspheres [16,17]. PLA and PLGA drug-loaded microspheres and NPs protect the drugs, aid their solubilization, and improve their bioavailability and targeted release [18]. However, the hydrophobicity of these two materials limits their use as pharmaceutical carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In this conditions, required some new strategy to treat or manage advanced liver cancer. This review concluded that there are some new strategies available such as ligand mediated active targeting, nano carrier based RES uptake and some molecular conjugates of targeting ligands and active drugs that applicable to target effectively and killed the actively proliferating cancer cells, 68,69 and the available targeting ligands such as asialoglycoprotein, lactose and mannose, liver cancer cell specific antibodies, aptamers, avimers, bile acid conjugation, Collagen Type VI Receptor, Collagen Type VI Receptor and others ligands were successfully used for targeting liver cancer and further can be used for targeting and deliver anticancer drug or drug which are used to treatment of liver diseases. 70…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo experiments showed that the use of anti-GPC3 polymeric NPs loaded with sorafenib inhibited HepG2 cell proliferation. erefore, this drug delivery system could be a potential tool for the targeted treatment of liver cancer [104].…”
Section: Journal Of Oncologymentioning
confidence: 99%